Suspensión de terapia de reemplazo renal continua e independencia de diálisis en falla renal aguda - Gacitúa M., Ignacio (Revista Hospital Clínico Universidad de Chile, 2020)
Renal replacement therapy (RRT) is a crucial form of extracorporeal support in critical patients that develop acute kidney injury. This therapy allows to gain solute and water control when the kidneys are not capable of doing it. Nevertheless, RRT techniques are not without risks, complications and costs. Under this point of view, is fundamental to be conscious of the indications of timing and, most importantly, weaning of the RRT. The unnecesary extension of these techniques can lead to increase morbidity, hospital stay, health care costs and complications. Unfortunately, randomized controlled studies are scarce and this paucity of data has lead to different predictive models based on retrospective studies. Creatinine clearence, urinary output and other novel biomarkers has been used to identify the best moment to safely stop RRT. In this review, we summarize the available evidence about secure weaning of RRT and the potential of novel urinary and serum biomarkers that can be used to guide therapeutic decisions in the future.